Implementasi Kripto-Steganografi Salsa20 dan BPCS untuk Pengamanan Data Citra Digital - Paulus Lucky Tirma Irawan; D.J. Djoko H. Santjojo; M. Sarosa (Jurnal EECCIS, 2014)
In this research, cryptography of SALSA20 stream cipher technique combined with BPCS steganography technique was used to enhance the security layer in mobile communication. SALSA20 technique has been proven as one of the best stream cipher algorithm candidate according to eSTREAM portfolio report in 2012. The combination of SALSA cryptography and BPCS steganography technique can provide more security layer of digital image data as the research objective. The results from this research showed that combination of SALSA20 and BPCS technique need average time of 19.400s for the encryption and 21.900s for decryption process. The average memory (RAM) usage of these two technique is about 23.354 MB/s for the encryption process and 36.057 MB/s for the decryption. The analysis of component MSE and PSNR show a good result with value of 16.21259 dB for the MSE component and +44.08686 dB for the PSNR, with color contrast intensity distribution of the output image nearly identical to the original cover image.Keywords—BPCS, Cryptography, SALSA20, Steganography.